Biological fixation and nitrogen transfer by three legume species in mango and soursop organic orchards - Paulino, Gleicia Miranda; Alves, Bruno José Rodrigues; Barroso, Deborah Guerra; Urquiaga, Segundo; Espindola, José Antonio Azevedo (Pesquisa Agropecuaria Brasileira, 2010)
The objective of this work was to evaluate the biological nitrogen fixation (BNF) and the N transfer derived from BNF of the legume species – Gliricidia sepium (gliricidia), Crotalaria juncea (sunnhemp) and Cajanus cajan (pigeon pea) – for an intercropped organic orchard with mango and soursop, through the 15N natural abundance method. The following intercropping systems were evaluated: mango and soursop with gliricidia; mango and soursop with sunnhemp; mango and soursop with pigeon pea; and mango and soursop as control. Gliricidia showed the highest BNF potential (80%) , followed by sunnhemp (64.5%) and pigeon pea (45%). After two sunnhemp prunes, 149.5 kg ha-1 of N per year were supplied, with 96.5 kg derived from BNF. After three annual prunes, gliricidia supplied 56.4 and 80.3 kg ha-1 of N per year, with 45 and 64 kg derived from BNF, in two consecutive years. The quantity of N supplied to the system was higher than the mango and soursop requirements. Variations in the natural abundance of 15N were found only in soursop leaves. Gliricidia and sunnhemp were prominent in N transfer, with approximately 22.5 and 40% respectively. Green manuring using gliricidia permits fractioning of the N supply, which is an advantage in N obtention by the fruit trees.